Investigation of dampness damage in the house of the lithuanian independence signatories/Lietuvos nepriklausomybės signatarų namų gedimų, susijusių su drėgme, natūriniai tyrimai - Ignatavičius, Česlovas (Journal of Civil Engineering and Management, 2001)
After the reconstruction of the House of the Lithuanian Independence Signatories the microclimate of its basement is damp, mycelium microorganisms, salt efflorescence occur on the enclosure wall surfaces, efflorescence and bubbles form on the facing of the walls and ceiling and an unpleasant smell appears in the building. Full-scale tests performed show that the protection of the basement exterior walls from damp is insufficient. On one spot of the outside ground the drained storm water penetrated through the basement exterior walls and streamed into the building after three hours from the beginning of the storm-water drainage. No water streams inside the building were observed at an other two storm-water drainage spots but the plaster humidity in the basement exterior walls inside the building was increased after the storm- water drainage on the outside ground. This dampness favoured the efflorescence of various salts on the facing of the basement walls and other building structures. Testing the basement air humidity showed that the relative air humidity in the middle of the basement space was 75.4–85.2%. It exceeds the maximum normative relative air humidity of 60%. The relative air humidity near the surfaces of the walls and floor was 95.3–100%. It exceeds the maximum normative relative air humidity of 80%. Such a high relative air humidity favoured the development of various mycelium microorganisms. Temperature analyses of the basement space showed that its air temperature differed from that of the wall and floor surfaces by up to 5.2°C and by up to 5.3°C, respectively. These temperature differencies exceed the maximum normative temperature difference of up to 2°C and up to 3°C for wall and floor surfaces, respectively. Such significant temperature differencies cause a great thermal discomfort. On the basis of the investigation results presented, it can be stated that the basement in the House of the Lithuanian Independence Signatories is unsuitable for a public building.Article in Lithuanian.First Published Online: 30 Jul 2012